Microwave-assisted hydrothermal synthesis of Ag-2(W1-xMox)O-4 heterostructures: Nucleation of Ag, morphology, and photoluminescence properties - Silva, M. D. P. (2016)
Ag2W1-xMoxO4 (x = 0.0 and 0.50) powders were synthesized by the co-precipitation (drop-by-drop) method and processed using a microwave-assisted hydrothermal method. We report the real-time in situ formation and growth of Ag filaments on the Ag2W1-xMoxO4 crystals using an accelerated electron beam under high vacuum. Various techniques were used to evaluate the influence of the network-former substitution on the structural and optical properties, including photoluminescence (PL) emission, of these materials. X-ray diffraction results confirmed the phases obtained by the synthesis methods. Raman spectroscopy revealed significant changes in local order-disorder as a function of the network-former substitution. Field-emission scanning electron microscopy was used to determine the shape as well as dimensions of the Ag2W1-xMoxO4 heterostructures. The PL spectra showed that the PL-emission intensities of Ag2W1-xMoxO4 were greater than those of pure Ag2WO4, probably because of the increase of intermediary energy levels within the band gap of the Ag2W1-xMoxO4 heterostructures, as evidenced by the decrease in the band-gap values measured by ultraviolet-visible spectroscopy. (C) 2015 Elsevier B.V. All rights reserved.